The Concept of treaty in Islamic Jurisprudence: A comparative view of the classical jurists - bsoul, Labeeb (Journal of Islam in Asia (E-ISSN 2289-8077), 2010)
This article aims to shed light on a particular area in the field of Islamic International law (siyar) treaty in Islamic jurisprudence. It addresses a comparative view of classical jurists of treaties both theoretically and historically and highlights their continued relevance to the contemporary world. Since the concept of treaty a lacuna in scholarship as well as the familiar of international legal theorists to study and integrate the Islamic treaty system into the body of modern international law in order to have a mutual understanding and respect and honor for treaties among nations. I would like to present a series of three parts the first one addresses the concept of treaty in Islamic jurisprudence the second addresses the process of drafting treaties and their conclusion and the third addresses selected treaties, including the treaty of Hudaybiya that took place between Muslims and non-Muslims..